1999
DOI: 10.1103/physreve.60.6519
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of the distribution of price fluctuations of individual companies

Abstract: We present a phenomenological study of stock price fluctuations of individual companies. We systematically analyze two different databases covering securities from the three major US stock markets: (a) the New York Stock Exchange, (b) the American Stock Exchange, and (c) the National Association of Securities Dealers Automated Quotation stock market. Specifically, we consider (i) the trades and quotes database, for which we analyze 40 million records for 1000 US companies for the 2-year period 1994-95, and (ii… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

40
363
6
4

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 517 publications
(413 citation statements)
references
References 28 publications
40
363
6
4
Order By: Relevance
“…Gopikrishnan et al (24)(25)(26)(27) recently acquired a data set 3 orders of magnitude larger still (of order 10 9 )-one that records every transaction of every stock. They found that when their data were graphed on log-log paper, the result was linearity.…”
Section: Statistical Features Of Price Fluctuationsmentioning
confidence: 99%
“…Gopikrishnan et al (24)(25)(26)(27) recently acquired a data set 3 orders of magnitude larger still (of order 10 9 )-one that records every transaction of every stock. They found that when their data were graphed on log-log paper, the result was linearity.…”
Section: Statistical Features Of Price Fluctuationsmentioning
confidence: 99%
“…for large n. The family of the scaling exponents h(q) can be then obtained by observing the slope of log-log plots of F q vs. n. h(q) can be considered as a generalization of the Hurst exponent H with the equivalence H ≡ h (2). Now the distinction between monofractal and multifractal signals can be performed: if h(q) = H for all q, then the signal under study is monofractal; it is multifractal otherwise.…”
Section: Methods and Datamentioning
confidence: 99%
“…The so-called financial stylized facts comprising, among others, the non-negligible fat tails of log-return distributions, volatility clustering and its long-time correlations, anomalous diffusion etc. [2,3,4,5] counter the above-mentioned fundamental assumptions of market dynamics challenging their applicability in practice. That the financial dynamics is more complex than it is commonly assumed can also be inferred from a number of recently-published papers discovering and exploring the multifractal characteristics of data from the stock markets [6,7,8,9,10], the forex markets [7,10,11,12,13] and the commodity ones [14].…”
Section: Introductionmentioning
confidence: 99%
“…Econophysics is an emerging interdisciplinary field, where theories, concepts, and tools borrowed from statistical mechanics, nonlinear sciences, mathematics, and complexity sciences are applied to understand the self-organized complex behaviors of financial markets [2,3,4]. Econophysicists have discovered or rediscovered numerous stylized facts of financial markets [2,5], such as fat tails of return distributions [6,1,7,8,9,10,11,12,13], absence of autocorrelations of returns [2], long memory in volatility [14,15,16], intermittency and multifractality [7,17,18,19], and leverage effect [20,21], to list a few.…”
Section: Introductionmentioning
confidence: 99%